Sexual selection towards a protamine expression ratio optimum in two rodent groups? - Arévalo, Lena (2021)
Post-copulatory sexual selection is thought to influence the evolution of genes involved in reproduction. However, the detection of straightforward effects has been proven difficult due to the complexity and diversity of reproductive landscapes found in different taxa. Here, we compare the possible effect of relative testes mass as a sperm competition proxy on protamine genotype (protamine 1/protamine 2 ratio) and the link to sperm head phenotype in two rodent groups, mice, and voles. In mice, protamine expression ratios were found to increase from low values toward a 1:1 ratio in a positive association with testes mass, and relative sperm head area. In contrast, in voles, decreasing protamine expression ratios were found in species with larger testes but, surprisingly, they range from high values, again toward a 1:1 ratio, and showing a negative correlation with relative sperm head area. Altogether, we found differences in the way protamines seem to be selected and involved in adaptations of the sperm head in voles and mice. However, sexual selection driven by sperm competition seems to exhibit a common evolutionary pattern in both groups toward an equilibrium in the expression of the two protamines.